Association between hemoglobin-to-red blood cell distribution width ratio and cognitive function in older US adults: a cross-sectional study based on the NHANES 2011–2014 - Wang, Fan; Wang, Xiangyang; Wang, Chaowei; Liu, Hao; Xu, Zhixiu; Li, Dongli; Zhao, Xiaowen; Zhao, Jialu; Li, Shaomin; Zhao, Jianhua (Frontiers in Aging Neuroscience, 2025)
IntroductionThe hemoglobin-to-red blood cell distribution width ratio (HRR) is acknowledged as a promising new prognostic biomarker. Nevertheless, investigations into its connection with cognitive function have yielded unclear results.AimThis study aimed to investigate the association between the hemoglobin-to-red blood cell distribution width ratio (HRR) and cognitive function in older adults in the United States.MethodsThis study utilized data obtained from the NHANES database, encompassing the years 2011 to 2014. The participant cohort consisted of elderly individuals aged 60 years and older, all of whom underwent thorough assessments of cognitive function, hemoglobin levels, and red blood cell width. We employed weighted logistic regression analysis, along with restricted cubic spline (RCS) curves and subgroup analyses, to rigorously evaluate the association between hemoglobin-to-red blood cell distribution width ratio (HRR) and cognitive function.ResultsThis study encompassed a total of 2,520 participants, with a mean age of 69.44 ± 6.76 years. After adjusting for multiple covariates, logistic regression analysis indicated a significant linear cognitive impairment between HRR and cognitive function. Specifically, each one-unit increase in HRR was associated with an 82% reduction in the probability of cognitive impairment among participants (OR = 0.18, 95% CI: 0.04–0.78). This relationship remained exist after HRR was categorized into tertiles. Participants in the highest HRR tertile exhibited a 42% lower likelihood of cognitive impairment compared to those in the lowest tertile (OR = 0.58; 95% CI: 0.37–0.91, p = 0.022). To validate the robustness of our findings, we conducted subgroup analyses, which consistently demonstrated stable results across all evaluated groups.ConclusionThis cross-sectional study revealed a significant negative correlation between HRR and cognitive function.